2019
DOI: 10.1186/s12934-019-1233-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and sequential based co-fermentations of Trichoderma asperellum GDFS1009 and Bacillus amyloliquefaciens 1841: a strategy to enhance the gene expression and metabolites to improve the bio-control and plant growth promoting activity

Abstract: BackgroundThe consequence of simultaneous and sequential inoculation of T. asperellum and B. amyloliquefaciens cultures with respect to growth rate, differential expression of vital genes and metabolites were examined.ResultsThe competition was observed between T. asperellum and B. amyloliquefaciens under co-cultivation. The proliferation of Trichoderma was reduced in the simultaneous inoculation (TB1) method, possibly due to the fastest growth of Bacillus. Both T. asperellum and B. amyloliquefaciens were prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…6). like T. asperellum GDFS1009 for Fusarium graminearum (Karuppiah et al 2019), and T. harzianum INAT11 for Fusarium verticillioides and Fusarium graminearum (Ferrigo et al 2020). The ameliorative role of Trichoderma under abiotic stress has been also confirmed by many investigations like treating wheat with Trichoderma longibrachiatum under salinity (10 and 20 g l −1 NaCl) as published by .…”
Section: Trichoderma Under Stressmentioning
confidence: 72%
“…6). like T. asperellum GDFS1009 for Fusarium graminearum (Karuppiah et al 2019), and T. harzianum INAT11 for Fusarium verticillioides and Fusarium graminearum (Ferrigo et al 2020). The ameliorative role of Trichoderma under abiotic stress has been also confirmed by many investigations like treating wheat with Trichoderma longibrachiatum under salinity (10 and 20 g l −1 NaCl) as published by .…”
Section: Trichoderma Under Stressmentioning
confidence: 72%
“…The co-cultivation with B. amyloliquefaciens offered differentiated cellular environs to induce the genes involved in metabolic pathways [11,12]. The metabolic pathway might comprise several enzymes, and these properties could vary depending on the circumstance.…”
Section: Discussionmentioning
confidence: 99%
“…The present investigations revealed that the overexpression of the Vel1 gene might induce the secondary metabolite producing genes of Trichoderma and mycoparasitism to upregulate the defense potential of plants. Previously, Karuppiah et al [12] evidenced that the co-culture stimulated the defense potential of plants against pathogens. Likewise, we observed that the TA OE-Vel1 + BA and TA + BA co-culture is improving the plant defense gene expression than the axenic cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations